Método para cálculo da impedância de malhas de aterramento típicos de torres de linhas de transmissão - Alexander Barros Lima (2010)
The unplanned outages that occur on a transmission line is one important parameter in defining their performance, being the lightning the main event responsible for such occurrences. A technique widely used as a preventive procedure is to reduce the impedance of grounding grids of the towers. To achieve this goal, preliminary studies conducted at the design stage should be supported by tools and computational models that adequately express the issues relating to the electromagnetic event. This work presents a method for defining a model for grounding grids typically found in transmission lines towers. It is based on the classical transmission line theory, giving it simplicity and low computational cost. The model considers the electromagnetic coupling between electrodes and the variation with frequency of the soil parameters, resistivity and permittivity, may be included. The implementation can be done in PSPICE thus this procedure becomes quite simple. Analysis were done in this simulation environment in time and frequency domain, where parameters of practical interest such as the frequency response, maximum voltage developed and impulsive impedance were easily obtained.